PENGARUH PENGALAMAN EKONOMI, KONTROL DIRI SERTA PENDAPATAN SISWA TERHADAP PERILAKU EKONOMI SISWA SMA DI KECAMATAN PASIR BELENGKONG KABUPATEN PASER - Faidah, Ning; Harti, Harti; Subroto, Waspodo Tjipto (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2018)
This study aims to analyze the influence of economic experience, self-control and income of high school students on the behavior of high school economics in Pasir Belengkong District Paser district. The population of this study are students of class X and XI High School year 2016/2017. Data collection techniques using documentation and questionnaire, the method of proportional random sampling. The result of the analysis shows that partially the student's income does not have significant effect on the economic performance while the economic experience and self-control have a significant and positive influence on the students economic behavior. While simultaneous economic experience, self-control and student income have a significant effect on student economic behavior. Positive influence is indicated by the provision of continuous economic experience through habituation and strong self-control of each individual determines the rational economic behavior of each student. Daily habits related to economic experience need to be improved and in subsequent research the control of information needs to be added